Impact of UI/UX on Shopee User Acceptance: A TAM Approach - Maulidia, Syaqilla; Camila, Naina; Husein, Fadhil; Purnama, Diki Gita (Universitas Bina Darma, 2025)
In the digital era, e-commerce platforms such as Shopee must continually improve their user interface (UI) and user experience (UX) to enhance user acceptance and competitiveness. This study analyzes the impact of UI/UX on user acceptance of the Shopee application using the Technology Acceptance Model (TAM), incorporating four variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Behavioral Intention to Use (BIU), and Actual System Use (ASU). A quantitative approach was applied, collecting data via questionnaire from a purposive sample of 90 active Shopee users in RT 002/07, Pela Mampang. Data were analyzed using SPSS 26, including validity, reliability, and hypothesis testing. The results show that PEOU significantly influences PU, while both PU and PEOU have a strong and significant effect on BIU, with PU demonstrating a slightly stronger influence. BIU also significantly affects ASU. These findings indicate that ease of use and perceived benefits are key drivers of user intention and actual usage behavior. The results provide practical implications for Shopee's design and development teams to prioritize enhancing ease of navigation, feature intuitiveness, and visual clarity to increase user engagement and system usage.